Antioxidant potential of oregano extract (Origanum vulgare L.) - Aranha, Caroline Pereira Moura [UNESP]; Jorge, Neuza [UNESP] (Emerald Group Publishing Limited, 2012)
Purpose - This research aims to evaluate the antioxidant potential of oregano extract (OE), as well as its isolated and synergistic effect when applied to soybean oil (SO) under thermal oxidation.Design/methodology/approach - In order to determine the antioxidant activity of oregano extract and its synergistic effect with tert-butylhydroquinone (TBHQ), thermal oxidation was performed using the following treatments: SO, SO with 50 mg/kg of TBHQ, SO with 3,000 mg/kg of OE, and SO with 3,000 mg/kg of oregano extract and 50 mg/kg of TBHQ (mixture). The treatments underwent heating at 180 degrees C for 20 hours, and analyses of oxidative stability, total polar compounds, tocopherols and fatty acids composition were performed. The results obtained were subjected to analysis of variance and Tukey test for averages at 5 percent, using the program ESTAT version 2.0.Findings - Considering the results of antioxidant activity and total phenolic compounds, it was possible to verify that the ethanolic extract of oregano has presented antioxidant potential. Furthermore, considering the results obtained in the analyses of oxidative stability, polar compounds, tocopherols and fatty acids profile, it was possible to,observe that the extract has prevented lipid oxidation when added to SO.Originality/value - The study offers information on the use of natural antioxidants as an alternative to the use of synthetic antioxidants, which can be considered toxic.
Keywords: Antioxidant activity; DPPH; Phenolic compounds; Polar compounds; Tocopherol; Fatty acids; Fats; Edible oils; Chemical properties of materials